Exclusive Man’s Fashion / Roslina Ibrahim ... [et al.] - Ibrahim, Roslina; Mohd Zawawi, Intan Rahidah; Yussof, Yusdiana; Shahidan, Asmawati; Abd Rahman, Siti Jamilah (2002)
Exclusive Man's Fashion is located at Lot 491, Bangunan Empayar, Jalan Tunku Ibrahim, 05000 Alor Setar, Kedah. Our boutique nearest the traffic light at the center of Alor Setar and it form by a partnership with contribute the equity and bank loan to build a capital about RM176288.53. According to the plan, our business is expected to be operated by JAN 2005 after all the agreement is expected. Our main activity is selling, rent, booking of clothes and consultant in fashion. As we know, our country's vision to become the industrial country during vision 2020. Government encourage bumiputera to take part in business although in small business beside to help bumiputera improve their life. So, the opportunity should be taken to become successful businessman or businesswoman. By the way, not many more bumiputera take part in business of man boutique but more in female boutique. Morever, as we can see, man likes a quality, branded and exclusive besides up to dates clothes. Besides that, business in men boutique give a great return according to the survey because not more competition in this business and it has a potential to success if good in management.